Oleoyl-lysophosphatidylcholine limits endothelial nitric oxide bioavailability by induction of reactive oxygen species. - Andrijana Kozina; Stefan Opresnik; Michael Sze Ka Wong; Seth Hallström; Wolfgang F Graier; Roland Malli; Katrin Schröder; Kurt Schmidt; Saša Frank (PLoS ONE)
Previously we reported modulation of endothelial prostacyclin and interleukin-8 production, cyclooxygenase-2 expression and vasorelaxation by oleoyl- lysophosphatidylcholine (LPC 18:1). In the present study, we examined the impact of this LPC on nitric oxide (NO) bioavailability in vascular endothelial EA.hy926 cells. Basal NO formation in these cells was decreased by LPC 18:1. This was accompanied with a partial disruption of the active endothelial nitric oxide synthase (eNOS)- dimer, leading to eNOS uncoupling and increased formation of reactive oxygen species (ROS). The LPC 18:1-induced ROS formation was attenuated by the superoxide scavenger Tiron, as well as by the pharmacological inhibitors of eNOS, NADPH oxidases, flavin-containing enzymes and superoxide dismutase (SOD). Intracellular ROS-formation was most prominent in mitochondria, less pronounced in cytosol and undetectable in endoplasmic reticulum. Importantly, Tiron completely prevented the LPC 18:1-induced decrease in NO bioavailability in EA.hy926 cells. The importance of the discovered findings for more in vivo like situations was analyzed by organ bath experiments in mouse aortic rings. LPC 18:1 attenuated the acetylcholine-induced, endothelium dependent vasorelaxation and massively decreased NO bioavailability. We conclude that LPC 18:1 induces eNOS uncoupling and unspecific superoxide production. This results in NO scavenging by ROS, a limited endothelial NO bioavailability and impaired vascular function.